Factors of Successful Social Pedagogical Activity: Empirical Conclusions - Švedaitė, Birutė (Acta Paedagogica Vilnensia, 2005)
The paper analyses the problem of success of social and educational activities. Qualitative expert research helped to reconstruct the key factors that determine the success of the social teaching in social aid organizations. The article also presents the methodology of expert interview survey, the possibilities of its application. A detailed description of the reconstructed factors of the expert survey that determine the success of the social teaching in the social aid organizations.
Keywords: social aid organizations; social teaching; social pedagogical activity; success